POLITICAL COMMUNICATION IN BUDGET DECISION-MAKING: EVIDENCE FROM THE SUPERVISORY FUNCTION OF COMMISSION D OF THE NORTH SUMATRA PROVINCIAL DPRD - Johan Wiryawan; Muhammad Tariq (Academic Solution Publisher, 2026)
Budget decision-making in regional legislative institutions is not merely administrative in nature, but is also influenced by the dynamics of political communication, such as informal communication, negotiation, and political lobbying. This phenomenon highlights the urgency of understanding the decision-making process more deeply, considering its impact on public accountability and development effectiveness. This study aims to analyze the role of political communication in budget decision-making within the oversight function of Commission D of the Regional House of Representatives (DPRD) of North Sumatra Province. The novelty of this study lies in the integration of a political communication perspective into budgetary analysis and the development of a thematic model that explains the relationship between communication, actor interaction, and decision-making. This study employs a qualitative approach with a case study design based on an interpretive approach. Data were collected through interviews, observation, and documentation, and were analyzed using thematic analysis. The results of the study show that informal communication plays a strategic role in building mutual understanding, while budget decisions are the result of social construction influenced by interaction and negotiation among actors.